An exploration of the heterogeneity in effects of SGLT2 inhibition on cardiovascular and all-cause mortality in the EMPA-REG OUTCOME, CANVAS Program, DECLARE-TIMI 58, and CREDENCE trials. (1st February 2021) - Yu, Jie; Zhou, Zien; Mahaffey, Kenneth W.; Matthews, David R.; Neuen, Brendon L.; Heerspink, Hiddo J.L.; Jardine, Meg J.; Li, JingWei; Perkovic, Vlado; Neal, Bruce; Arnott, Clare
Abstract: Background: Large-scale outcome trials of sodium glucose co-transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes have identified consistent effects on major adverse cardiovascular events, heart failure, and progression of kidney disease. However, the magnitude of effects on cardiovascular and all-cause death appeared to vary between some of the studies. Methods: We explored the impact of differences in trial methodologies, participant characteristics, types of deaths, follow-up duration, effects on intermediate markers of risk, and drug selectivity for SGLT2 on the magnitude of the protective effect against fatal events achieved in the 4 trials. Results: The trial populations differed substantively in the proportions with baseline atherosclerotic cardiovascular disease history (99.2% in EMPA-REG OUTCOME to 40.6% in DECLARE-TIMI 58), and macroalbuminuria (88.0% in CREDENCE to 7.6% in the CANVAS Program). Meta-regression analyses identified no clear effect of these (both P  > 0.09) or other participant characteristics on mortality benefits (all P  > 0.55). Other differences between the trials (duration, selectivity of the SGLT2 inhibitor, or effects on intermediate markers of risk) also did not explain the heterogeneity in effects on mortality observed (all P  > 0.30). Conclusion: No clear explanation for the statistical evidence of heterogeneity in effects of SGLT2 inhibition on fatal outcomes between the trials could be identified. While the analyses had limited statistical power, these results raise the possibility that the observed variations in treatment effects on fatal outcomes between trials may be at least partly due to chance. Highlights: Heterogeneity in mortality was observed in large-scale trials of SGLT2 inhibitors. Meta-regression analyses found no explanation for variations in fatal outcomes. Variations in SGLT2 inhibitor effects on fatal outcomes may be partly due to chance.